OP0127 DISEASE PRESENTATION OF 1, 312 CHILDHOOD-ONSET SYSTEMIC LUPUS ERYTHEMATOSUS: INFLUENCE OF ETHNICITY. (June 2019) - Campos, Lucia; Fiorot, Fernanda; Islabão, Aline G.; Pereira, Rosa M.; Tererri, Maria T.; Saad-Magalhães, Claudia; Novak, Glaucia V.; Molinari, Beatriz; Sakamoto, Ana Paula; Aikawa, Nadia; Peracchi, Octávio; Appenzeller, Simone; et al.
Abstract : Background: To our knowledge the influence of ethnic background in childhood-onset SLE (cSLE) presentation was not evaluated in a large population of Latin American country. Objectives: To assess demographic data, clinical manifestations, laboratory abnormalities and disease activity score in cSLE patients according to ethnic groups at diagnosis Methods: This multicenter study included cSLE patients(ACR criteria) followed in 27 Pediatric Rheumatology services of Brazil. Ethnicities were classified in four groups according to the parents' and all four grandparents' self-reported ethnicity. The statistical analysis was performed using the Bonferroni's correction(p<0.0027). Results: According to ethnic groups, 1, 537 cSLE patients were classified in: Caucasian (n=786), African-Latin American(n=526), Asian(n=8) and others/unknown(n=217). Comparisons between 1, 312 African-Latin American and Caucasian revealed similar median age at cSLE diagnosis[12.2(2.6-18) vs. 12.1(0.3-18) years, p=0.234], time interval to diagnosis[0.25(0-12) vs. 0.3(0-10) years, p=0.034] and SLEDAI-2K score[14(0-55) vs. 14(0-63), p=0.781] in both groups. The mean number of diagnostic criteria according to SLICC(6.47±1.911 vs. 5.81±1.631, p<0.0001) and frequencies of maculopapular lupus rash (8% vs. 3%, p<0.0001), palate oral ulcers(17% vs. 11%, p=0.001), tongue oral ulcers (4% vs. 1%, p=0.001) and nonscarring alopecia(29% vs. 16%, p<0.0001) were significantly higher in African-Latin American, whereas malar rash(45% vs. 58%, p<0.0001) was more frequent in Caucasian. The presence of antiphospholipid antibody(23% vs. 12%, p<0.0001), low complement levels(58% vs. 41%, p<0.0001) and isolated direct Coombs test (10% vs. 5%, p=0.001) were also significantly higher in the former group. Conclusion: Our study demonstrated that disease presentation severity of African-Latin American cSLE patients is comparable to Caucasian. Mucocutaneous manifestations and autoantibodies profile were the only distinctive features of the former group. The unique mixed background of Brazilian patients probably minimized race diversity spectrum of these patients. Disclosure of Interests: None declared